2021
DOI: 10.1177/03635465211036471
|View full text |Cite
|
Sign up to set email alerts
|

Platelet-Rich Plasma Augmentation of Meniscal Repair in the Setting of Anterior Cruciate Ligament Reconstruction

Abstract: Background: The increasing incidence of anterior cruciate ligament (ACL) and meniscal injuries has led to strong interest in discovering new methods to enhance the biological healing response of these tissues. Platelet-rich plasma (PRP) contains various growth factors associated with a positive healing response, but few existing clinical studies are available to determine the risks and benefits of these therapies. Purpose: To determine the effects of intraoperative PRP on postoperative knee function and compli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 31 publications
0
19
0
Order By: Relevance
“…The use of PRP also had negative consequences in terms of the postoperative recovery of knee range of motion. Based on these data, the authors stated that orthopedic surgeons should cautiously consider the application of PRP during surgery for intra-articular knee injuries [18]. In a systematic review and meta-analysis published in 2021, Lv et al concluded that the use of PRP could significantly decrease pain in the short term but not in the long term [80].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The use of PRP also had negative consequences in terms of the postoperative recovery of knee range of motion. Based on these data, the authors stated that orthopedic surgeons should cautiously consider the application of PRP during surgery for intra-articular knee injuries [18]. In a systematic review and meta-analysis published in 2021, Lv et al concluded that the use of PRP could significantly decrease pain in the short term but not in the long term [80].…”
Section: Discussionmentioning
confidence: 99%
“…It is important to highlight the discrepancy between 2 recent articles: one on an experimental study stating that orthobiologics can accelerate biological events related to tendon allograft incorporation [72] and another on a clinical study on meniscal repair in the ACLR setting stating that the added use of intraoperative PRP does not improve the analyzed parameters (self-reported knee function, functional performance, and time to return to previous activity). According to Hexter et al, the use of PRP might have negative consequences for the postoperative recovery of knee range of motion [18].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations